2008
DOI: 10.1212/01.wnl.0000335970.78664.36
|View full text |Cite
|
Sign up to set email alerts
|

Subcutaneous IGF-1 is not beneficial in 2-year ALS trial

Abstract: Background Previous human clinical trials of insulin-like growth factor type I (IGF-1) in amyotrophic lateral sclerosis (ALS) have been inconsistent. This phase III, randomized, double-blind, placebo-controlled study was undertaken to address whether IGF-1 benefited patients with ALS. Methods A total of 330 patients from 20 medical centers were randomized to receive 0.05 mg/kg body weight of human recombinant IGF-1 given subcutaneously twice daily or placebo for 2 years. The primary outcome measure was chang… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
132
1
2

Year Published

2009
2009
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 229 publications
(136 citation statements)
references
References 21 publications
(19 reference statements)
1
132
1
2
Order By: Relevance
“…IGF‐1 is known to have a neurotrophic effect on motor neurons 30. To date IGF‐1 ‐based therapies have little beneficial effect upon systemic or intrathecal administration in ALS patients 19, 20, 21. The poor outcomes of these studies may possibly be due to low availability of IGF‐1 as free IGF‐1 is reduced while IGF‐1 R expression is upregulated in both the CNS and muscle of ALS patients 31, 32.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…IGF‐1 is known to have a neurotrophic effect on motor neurons 30. To date IGF‐1 ‐based therapies have little beneficial effect upon systemic or intrathecal administration in ALS patients 19, 20, 21. The poor outcomes of these studies may possibly be due to low availability of IGF‐1 as free IGF‐1 is reduced while IGF‐1 R expression is upregulated in both the CNS and muscle of ALS patients 31, 32.…”
Section: Discussionmentioning
confidence: 99%
“…In recent years, many studies have focused on gene delivery of growth factors to the central nervous system (CNS) in order to slow disease progression in animal models of ALS utilizing the intramuscular,10, 11, 12, 13 intracerebral,14, 15 intracerebroventricular16, and intraspinal17, 18 routes of administration. Despite the encouraging results of these studies, subcutaneous delivery of recombinant human insulin‐like growth factor 1 IGF‐1 ( rhIGF‐1) in ALS patients had little effect in 3 clinical trials 19, 20, 21. Each of these approaches has its own limitations which may negate achieving efficacy in ALS patients.…”
Section: Introductionmentioning
confidence: 99%
“…Thus, for example, AAV vectors injected into brains to deliver NGF in Alzheimer's disease [248], neurturin or glia cell-derived neurotrophic factor (GDNF) in Parkinson's disease [249,250], and insulin-like growth factor I in ALS [251] have proven safe, but with no demonstrable benefit. This apparent lack of benefit may relate to the late stage of the diseases at the time of treatment, the progressive nature of the diseases and/or the inability to quantitate minor benefit with lack of a robust biomarker [201].…”
Section: Changing the Brain Environmentmentioning
confidence: 99%
“…There have been several treatment trials using free IGF-1 therapy in amyotrophic lateral sclerosis (ALS) [68][69][70] and one trial of free IGF-1 complexed with IGF-1 binding protein-3 in myotonic dystrophy [71]. ALS trials failed to show a clear beneficial result but demonstrated safety of IGF-1 in these patients.…”
Section: Insulin-like Growth Factormentioning
confidence: 99%